The health condition of the first year students of the University of Zagreb - Fučkar Reichel, Ksenija (Array, 2010)
Student population today is defined by current social events and is therefore facing great physical and mental demands caused by a sedentary way of living. The World Health Organization’s researches show that inactivity and a sedentary way of life are some of the ten leading global causes of death and illness, and that physical activity contributes to the preservation and enhancement of health. The level of physical activity is changing throughout life, and increasingly drops at the time of schooling, especially in urban areas Locomotive system problems, as well as other health problems, are rapidly increasing in the period of childhood and adolescence. The objective of this research is to subjectively evaluate the health of students at the University of Zagreb. This research includes 796 first-year students of both genders. The results show the arithmetical mean, standard deviation and t-test for independent samples. The grading was provided by a questionnaire about health problems that consisted of multiple choice answers on a scale from 1 to 5 (from none to extreme). T-test shows statistically significant differences (p<.01 ; p<.05) between female and male students in the magnitude of the expressed problems and disorders. The most common health issues are: blood pressure, circulation, headaches, migraines, and lack of energy/constant fatigue. In the second place is locomotive system problems and spine deformations. The results show increased level of student health problems and imply the importance of regular physical activity that allows young people to have very important physical, mental, emotional and social wellbeing. It also contributes to better mental health, increase of self-confidence and concentration as well as decrease of symptoms of depression, possible stress and anxiety.